Optimization of biodiesel production from castor oil by Taguchi design. Issue 2 (April 2018) - Karmakar, Bisheswar; Dhawane, Sumit H.; Halder, Gopinath
Highlights: The inedible castor oil was used as a feedstock for synthesis of RCME. The L16 Taguchi approach was adopted to optimize the esterification process. Methanol to oil ratio emerged as a most influential parameter affecting FFA conversion. Esterification process follows pseudo-first order kinetics and requires low activation energy. Fuel characterization results revealed the acceptability of the RCME. Abstract: Development of a renewable substitute for petroleum fuels is needed to address the current scenario of the rising fuel crisis affecting transportation, growing concerns regarding environmental pollution as well as exhaustion of natural oil reserves. Keeping this in mind, an experimental investigation was undertaken to synthesize biodiesel from inedible commercial grade castor ( Ricinus communis ) oil. The feedstock was subjected to esterification under the experimental conditions suggested by L16 Taguchi orthogonal approach. Compared to heterogeneous sulfonated carbon catalysis, maximum FFA conversion of 90.83% was obtained with homogeneous acid catalyst under the following optimized conditions: reaction temperature of 50 °C, reaction duration of 1 h, catalyst concentration of 1% w/w, methanol to oil ratio of 20:1 and agitation speed of 700 rpm. Identification of noteworthy parameters were carried out employing Taguchi approach and emerged significant parameters were: molar ratio of oil to methanol, agitation speed, reaction temperature and catalyst concentration with contribution factors of 59.6%, 16.95%, 12.59% and 10.82% respectively. Statistical analysis using ANOVA (analysis of variance) showed that the obtained results are in reasonable agreement with the predicted values. Kinetic studies showed that the esterification follows pseudo-first order kinetics with reaction rate constant of 0.0392 min −1 and activation energy of 8.184 kJ/mol. Fuel characterization results confirmed that the RCME ( Ricinus communis methyl ester) properties are comparable to petro-diesel and within ASTM limits. Hence, the optimization employing L16 Taguchi approach yielded the best parametric conditions for the cost-effective synthesis of biodiesel from castor oil through single step acid esterification.